Notes on some tardigrades from Central Africa, with the description of a new species of Hypsibiidae - Pilato, Giovanni; Binda, Maria Grazia; Lisi, Oscar (Zootaxa, 2003)
Eight species of African tardigrades are reported, including a new species. Hypsibius multituberculatus sp. n. has many small cuticular dorsal and lateral tubercles, two macroplacoids and septulum, and a cuticular bar-like thickening between the claws on the hind legs. Other species reported are Echiniscus pusae, Macrobiotus iharosi, Macrobiotus vanescens, Macrobiotus ragonesei, Isohypsibius sattleri, Hypsibius dujardini and Milnesium tardigradum.